N'-(3,5-Di-tert-butyl-4-hydroxybenzylidene)-2-hydroxybenzohydrazide methanol solvate - Ariffin, Azhar; Ng, S.W.; Yehye, W.A. (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, C22H28N2O3 center dot CH4O, consists of two independent Schiff base molecules and two independent methanol solvent molecules. In one Schiff base molecule, the 2-hydroxy group forms an intramolecular hydrogen bond with the amide O atom, whereas in the other Schiff base molecule, the 2-hydroxy-substituted benzene ring is oriented so that the 2-hydroxy group serves as hydrogen-bond acceptor for the amide NH group. In the crystal structure, Schiff base molecules interact with methanol solvent to furnish a hydrogen-bonded chain.